Free fatty acids support oligodendrocyte survival in a mouse model of amyotrophic lateral sclerosis - Maruyama, Takashi; Tanabe, Shogo; Uyeda, Akiko; Suzuki, Tatsunori; Muramatsu, Rieko (Frontiers in Cellular Neuroscience, 2023)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by the white matter degeneration. Although changes in blood lipids are involved in the pathogenesis of neurological diseases, the pathological role of blood lipids in ALS remains unclear. We performed lipidome analysis on the plasma of ALS model mice, mutant superoxide dismutase 1 (SOD1G93A) mice, and found that the concentration of free fatty acids (FFAs), including oleic acid (OA) and linoleic acid (LA), decreased prior to disease onset. An in vitro study revealed that OA and LA directly inhibited glutamate-induced oligodendrocytes cell death via free fatty acid receptor 1 (FFAR1). A cocktail containing OA/LA suppressed oligodendrocyte cell death in the spinal cord of SOD1G93A mice. These results suggested that the reduction of FFAs in the plasma is a pathogenic biomarker for ALS in the early stages, and supplying a deficiency in FFAs is a potential therapeutic approach for ALS by preventing oligodendrocyte cell death.